Geschichtsmythen über Hispanoamerika Entdeckung, Eroberung und Kolonisierung in deutschen und österreichischen Schulbüchern des 21. Jahrhunderts - Bernhard, Roland
There are numerous popular myths concerning Hispanic America in German and Austrian textbooks from the first decade of the 21st century, and thus there is a big gap between historical narratives in textbooks and the scientific historical discourse. An analysis of textbooks from four centuries shows, that some of the myths were introduced into the textbooks in the twentieth century - for example the "myth of the flat earth" of medieval times. The myths relating to Hispanic America and the images and assumptions they conveyed were important to many different groups throughout history, became incorporated into collective memory and were uncritically incorporated into German and Austrian textbooks.